Pengaruh Corporate Social Responsibility, Struktur Modal, dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Rafa Azzahra; Renea Shinta Aminda; Muhammad Nur Rizqi (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aims to determine the effect of Corporate Social Responsibility, Capital Structure, and Company Size on Company Value. The population used in this study are coal sub-sector companies listed on the Indonesia Stock Exchange in 2018-2022. The sample in this study was obtained using purposive sampling technique and companies that meet the sample selection criteria are 8 companies. The data source used in this study uses secondary data in the form of annual reports of coal sub-sector companies. The results of the study indicate that Corporate Social Responsibility does not have a significant effect on company value, Capital Structure has a negative and significant effect on company value, Company Size has a positive and significant effect on company value, and Corporate Social Responsibility, Capital Structure, and Company Size simultaneously show that there is a significant effect on company value.